Perfil de expressão de citoqueratina 17 e anexina A2 em modelo celular da doença hepática gordurosa associada ao metabolismo - Azevedo, Gabriela Tolentino (2024)
Obesity and metabolic-associated fatty liver disease (MAFLD) have increased, becoming a public health problem, including in Brazil. Excessive accumulation of body fat is a risk factor for metabolic syndromes, demonstrating a close relationship between the two conditions. However, the molecular profile of obesity and MAFLD is still poorly known and is essential for understanding their genesis and therapeutic targeting. Thus, the present study aimed to evaluate the expression profile of two new markers Cytokeratin 17 (KRT17) and Annexin A2 (ANXA2) in a cellular model of MAFLD. For this, lipid accumulation was induced by exposing HepG2 cells to isolated palmitate at 0.7 mM (P), to oleic and palmitic fatty acids in a 2:1 ratio, defined as OP1 at a final concentration of 1 mM and OP2 at final concentration of 2 mM. The lipids were conjugated with bovine serum albumin (BSA) for 24 hours. As a control, cells were incubated with vehicle (BSA-conjugated DMEM containing ethanol). qRT-PCR and Western Blotting assays were conducted to observe the transcriptional modulation of KRT17 ANXA2 and the cytokines IL1β, IL17, IL22, TGFβ, IL6 and STAT3. The results revealed that there was intracellular accumulation of lipids in all treatments. In OP2, ANXA2 expression increased significantly. IL-1β, IL-17, IL-22, TGF-β, IL-6 and STAT3 transcripts were also significantly increased in the OP2 group, demonstrating an inflammatory process associated with MAFLD when fatty acids are added at the final concentration 2mM. There was an increase in the cytoplasmic protein expression of ANXA2 in OP1 and OP2, with no significant difference in the nucleus. The expression of KRT17 decreased significantly in the cytoplasm in OP1 and OP2 treatments. Thus, under conditions of steatosis due to lipid accumulation in HepG2 cells, an inflammatory process occurs accompanied by an increase in KRT17 and ANXA2 transcripts and a differential protein behavior, with an increase in ANXA2 in the cytoplasm and a decrease in KRT17, which can translocate to the nucleus Therefore, the cytokines-KRT17/ANXA2 axis may be a promising target in understanding metabolic disorders, especially MAFLD.